Financing of media firms: Does competition matter? - Hans Jarle Kind; Tore Nilssen; Lars Sørgard (University of Oslo, Department of Economics, 2005)
This paper analyses how competition between media firms influences the way they are financed. In a setting where monopoly media firms choose to be completely financed by consumer payments, competition may lead the media firms to be financed by advertising as well. The closer substitutes the media firms' products are, the less they rely on consumer payment and the more they rely on advertising revenues. If media firms can invest in programming, they invest more the less differentiated the media products are perceived to be.
Keywords: L22; L82; L86; M37; 330; Media; Advertising; Two-sided markets; Medienwirtschaft; Duopol; Monopol; Unternehmensfinanzierung; Werbung